2015
DOI: 10.3109/10428194.2015.1070151
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of rituximab in addition to fludarabine and cyclophosphamide (R-FC) for the first-line treatment of chronic lymphocytic leukemia

Abstract: The cost-effectiveness of rituximab in combination with fludarabine/cyclophosphamide (R-FC) for the first line treatment of chronic lymphocytic leukemia (CLL) was evaluated. Based on long-term clinical data (follow-up of 5.9 years) from the CLL8-trial, a Markov-model with three health states (Free from disease progression, Progressive disease, Death) was used to evaluate the cost per quality-adjusted life-year (QALY) and cost per life years gained (LYG) of R-FC from the perspective of the German statutory heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In DLBCL, various groups report that R-CHOP (rituximab with cyclophosphamide, doxorubicin, vincristine, and prednisone) results in a QALY gain of between 0.82 and 1.07 QALYs compared with CHOP alone, over a 15-year time horizon [8991]. In CLL, when RTX is added to fludarabine and cyclophosphamide (FC), QALYs increase to 1.127 (assuming an effect for 5.9 years) and to 1.459 (assuming an effect for 10 years) compared with FC alone [92]. Another study found the addition of RTX to FC led to an incremental gain of 0.94 QALYs in a 15-year horizon [93].…”
Section: Discussionmentioning
confidence: 99%
“…In DLBCL, various groups report that R-CHOP (rituximab with cyclophosphamide, doxorubicin, vincristine, and prednisone) results in a QALY gain of between 0.82 and 1.07 QALYs compared with CHOP alone, over a 15-year time horizon [8991]. In CLL, when RTX is added to fludarabine and cyclophosphamide (FC), QALYs increase to 1.127 (assuming an effect for 5.9 years) and to 1.459 (assuming an effect for 10 years) compared with FC alone [92]. Another study found the addition of RTX to FC led to an incremental gain of 0.94 QALYs in a 15-year horizon [93].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pharmacoeconomic analyses of rituximab have been conducted in the last 20 years that show rituximab is a cost-effective option compared with reference interventions for the treatment of B-cell hematologic malignancies, with the incremental cost-effectiveness ratios consistently at or below national willingness-to-pay thresholds. Table 5 presents a summary of the key findings from analyses published between 2010 and 2016, specifically evaluating the cost-effectiveness of intravenously administered rituximab for the treatment of FL [ 147 154 ], DLBCL [ 155 157 ], and CLL [ 158 161 ]. These studies were performed in a variety of countries (including several European countries, the USA, Canada, and Australia) from either a payer perspective or a societal perspective.…”
Section: Pharmacoeconomic Considerationsmentioning
confidence: 99%
“…In one analysis based on data from a large observational cohort of DLBCL patients in the USA, previously reported cost savings associated with rituximab-related survival benefits in clinical trials were not realized; according to the study authors, this finding was consistent with an ongoing accrual of medical costs associated with multiple comorbidities among elderly cancer survivors treated with rituximab [ 156 ]. Cost-effectiveness analyses of rituximab in CLL evaluated rituximab therapy plus chemotherapy versus chemotherapy alone in patients with previously untreated and relapsed/refractory disease [ 158 161 ]. In both settings, rituximab therapy plus chemotherapy was considered cost-effective, although in the Ukraine this was considered applicable only under conditions of economic stability, cost-effectiveness threshold growth, or with rituximab price negotiations [ 160 ].…”
Section: Pharmacoeconomic Considerationsmentioning
confidence: 99%
“…The economic burden of CLL has several dimensions. From the payer perspective, there are numerous health economic studies in CLL that could demonstrate the cost‐effectiveness of pharmacological treatments strategies . This analysis is focused on a hospital management perspective.…”
Section: Discussionmentioning
confidence: 99%
“… reported mean direct medical costs of €9331 per year per person while inpatient costs were €3453 followed by pharmaceuticals (€2699) and outpatient costs (€1699). Cost‐effectiveness modeling studies were published for pharmacological treatment , but hospital management‐focused assessments are still lacking. In addition, there is large variability in hospital costs and diagnosis‐related group (DRG) reimbursement throughout European countries , impeding direct transfer from economic data between these countries.…”
mentioning
confidence: 99%